2016
DOI: 10.1136/bmjopen-2016-014007
|View full text |Cite
|
Sign up to set email alerts
|

Young people's experiences of persistent musculoskeletal pain, needs, gaps and perceptions about the role of digital technologies to support their co-care: a qualitative study

Abstract: ObjectiveTo investigate young people's experiences of persistent musculoskeletal pain, including care needs and current service gaps as well as perceptions about the role of digital technologies to support their co-care.MethodsA qualitative study employing two independent data collection modes: in-depth individual semistructured interviews and focus groups.SettingCommunity settings throughout Australia.ParticipantsParticipants were included if they had experienced persistent musculoskeletal pain of >3-month du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 54 publications
1
42
0
Order By: Relevance
“…In these reviews, a limited number of trials are of some relevance to multimorbidity/comorbidity that includes a musculoskeletal condition with only a subset of the population under the age of 65 years, these interventions show some limited, small or mixed benefits across a range of health outcomes [5155]. It is therefore perhaps unsurprising that adults and younger people with musculoskeletal conditions [56, 57] identify a number of unmet healthcare service and information needs. These unmet needs can help inform improvements to existing models of care and furthermore emphasise the need to involve consumers in implementation of models of care.…”
Section: Discussionmentioning
confidence: 99%
“…In these reviews, a limited number of trials are of some relevance to multimorbidity/comorbidity that includes a musculoskeletal condition with only a subset of the population under the age of 65 years, these interventions show some limited, small or mixed benefits across a range of health outcomes [5155]. It is therefore perhaps unsurprising that adults and younger people with musculoskeletal conditions [56, 57] identify a number of unmet healthcare service and information needs. These unmet needs can help inform improvements to existing models of care and furthermore emphasise the need to involve consumers in implementation of models of care.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major causes of disability in UAE is the musculoskeletal diseases [12]. The trouble of persistent musculoskeletal pain is significantly important in young adults, making their lives more difficult and challenging [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also demonstrated that adolescents with pain experience problems because the pain is invisible, and therefore might be difficult for others to understand. Thus, AYAs might experience a lack of support and empathy because the pain is not visible and not related to a disease [50,51]. Moreover, impaired education performance is problematic for AYAs with chronic pain, and studies have shown that dropout and absence from school among AYAs are increasing.…”
Section: Juggling Pain With Everyday Lifementioning
confidence: 99%